The Role of Customer Satisfaction in Mediating the Influence of Product Quality on Generation Z Consumer Loyalty in Kopi Kenangan in Makassar City - Nurman (Economics and Business Journal (ECBIS), 2026)
The Influence of Product Quality on Customer Loyalty with Customer Satisfaction as a Mediating Variable in Gen Z Consumers of Kopi Kenangan in Makassar City. Thesis, Management Study Program, Faculty of Economics and Business, Makassar State University. Guided by Mr. Anwar and Mr. Muhammad Ichwan Musa. This study aims to determine the influence of product quality on customer loyalty with customer satisfaction as a mediating variable in Generation Z consumers of Kopi Kenangan in Makassar City. The focus of this research is to analyze how product quality can increase customer satisfaction and shape customer loyalty. This type of research uses a quantitative approach with explanatory associatives. Data was collected through a questionnaire to 110 respondents who are Gen Z consumers of Kopi Kenangan in Makassar City. The data analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS application version 4.0.9.9. to test relationships between variables. The results of the study show that product quality has a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty and acts as a mediating variable in the relationship between product quality and customer loyalty. These findings show that good product quality can increase satisfaction and strengthen the loyalty of Kopi Kenangan customers in Makassar City.